Aerospace series. Sleeving, heat-shrinkable, for binding, insulation and identification. polyvinylidene fluoride (PVDF) Identification sleeves. Operating Temperature range -55ºC to 225ºC. Product Standard Part 203, (11th January 2023) - British Standards Institution,
No abstract available